Hubungan Spiritualitas Guru Pendidikan Agama Kristen (PAK) dan Penelaahan Alkitab (PA) Terhadap Pembentukan Karakter Kristiani Siswa di SMP Negeri di Kecamatan Rimbo - Grace Skinantha S; Johari Manik; Hanna Dewi Aritonang; Sudirman Lase; Iwan Setiawan Tarigan (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to 1) find out whether there is a relationship between the Spirituality of PAK Teachers and the Christian Character Formation of Teb State Middle School Students, 2) find out whether there is a relationship between Bible Study and the Christian Character Formation of Tebo State Middle School Students, 3) to find out whether there is a relationship between the Spirituality of PAK Teachers and Bible Study on the Formation of the Christian Character of Shiva SMP N Tebo. The research hypothesis is: